(untitled) - Martina Tomagová; Juraj Čáp; Lucia Podolinská (University of Ostrava, 2024)
Aim: The idiographic case study aimed to explore the trust of a person with chronic pancreatitis in healthcare professionals. Design: An interpretive phenomenological idiographic case study. Methods: Data collection was carried out through a semi-structured in-depth interview with a 29-year-old man with chronic pancreatitis. The purposive sampling of the participant was carried out according to feasibility criteria. Interpretative phenomenological analysis was used with the assistance of Atlas.ti 9 for data analysis. Results: Five interconnected personal experiential themes reflecting the trust of the participant in healthcare professionals were identified: Trust in healthcare professionals as an inner feeling; Active and partnership approach of healthcare professionals; Paternalistic approach and lack of interest of healthcare professionals in the patient; Expertise of healthcare professionals; and Linking trust in health professionals with the hospital ward environment, with 22 experiential statements. Conclusion: The participant considered trust to be an internal feeling of expectation that healthcare professionals would help him actively solve his health problems. The findings promote the implementation of patient-centered care and the partnership approach in the care of patients with chronic pancreatitis. The personal experience themes identified provide information for further qualitative research aimed at a deeper understanding of the lived experience of trust for patients with chronic pancreatitis.